2002
DOI: 10.1074/jbc.m201095200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Induces Hypoxia-inducible Factor-1α Stabilization and Nuclear Localization in a Human Prostate Cancer Cell Line

Abstract: Hypoxia-induced up-regulation of vascular endothelial growth factor (VEGF) expression is a critical event leading to tumor neovascularization. Hypoxia stimulates hypoxia-inducible factor-1α (HIF-1α), a transcriptional activator of VEGF. Cyclooxygenase (COX)-2, an inducible enzyme that catalyzes the formation of prostaglandins (PGs) from arachidonic acid, is also induced by hypoxia. We reported previously that COX-2 inhibition prevents hypoxic up-regulation of VEGF in human prostate cancer cells and that prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
148
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(160 citation statements)
references
References 43 publications
11
148
1
Order By: Relevance
“…5B, exposure of GFP-HIF1a/EMT6 cells to 10 Amol/L PGE 2 induced nuclear translocation of the GFP-tagged HIF-1a protein. This is in excellent agreement with the findings of Liu et al (17), who showed that PGE 2 exposure resulted in significant nuclear localization of HIF-1a in PC-3ML human prostate cancer cells under normoxic conditions. We find that Photofrin-PDT also strongly induced the translocation of the fusion protein from the cytosol to the nucleus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…5B, exposure of GFP-HIF1a/EMT6 cells to 10 Amol/L PGE 2 induced nuclear translocation of the GFP-tagged HIF-1a protein. This is in excellent agreement with the findings of Liu et al (17), who showed that PGE 2 exposure resulted in significant nuclear localization of HIF-1a in PC-3ML human prostate cancer cells under normoxic conditions. We find that Photofrin-PDT also strongly induced the translocation of the fusion protein from the cytosol to the nucleus.…”
Section: Discussionsupporting
confidence: 82%
“…The fusion protein vector was a gift from Alice Levine (Mount Sinai Medical School, New York, NY) and was prepared by fusing HIF-1a cDNA to the pEGFP (Clontech; ref. 17). The transfection and clone selection procedures were similar to those followed for the 5HRE-GFP/EMT6 cells.…”
Section: Cell Linesmentioning
confidence: 99%
“…In vitro studies suggested that the COX-2 gene has a hypoxic responsive element and that hypoxia induces the expression of COX-2 mRNA and its protein in human vascular endothelial cells. Liu et al 54 proposed that inhibitors of the COX enzymes prevent angiogenesis by stabilizing HIF-1␣ accumulation under hypoxic conditions. 54 This proposed mechanism is not supported by our findings, which showed a negative statistical correlation between COX-2 expression and HIF-1␣.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al 54 proposed that inhibitors of the COX enzymes prevent angiogenesis by stabilizing HIF-1␣ accumulation under hypoxic conditions. 54 This proposed mechanism is not supported by our findings, which showed a negative statistical correlation between COX-2 expression and HIF-1␣. In normoxia, the HIF-1␣ protein is maintained at low and often undetectable levels and is overexpressed under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β and HGF regulate COX-2 expression in breast and colon carcinoma cells, respectively, and hypoxia potentiates HGFdependent PGE 2 release in colorectal cancer [16,32]. PGE 2 participates in nuclear translocation of exogenously expressed HIF-1α in prostate carcinoma cells [33]. COX-2 inhibition largely prevents MDA-MB231 bone metastasis by decreasing osteoclast number and increasing apoptosis [16].…”
Section: Involvement Of Cox-2-signaling Pathway In the Hypoxic Responsementioning
confidence: 99%